Investigation on the causes of speaking anxiety among PTPL college students / Norhafizah Abdul Halil - Abdul Halil, Norhafizah (2010)
Speaking anxiety is not a new phenomenon that needs to be faced by second language learners. The feelings of nervous, stress and uneasiness to speak using a language that is different from their mother tongue has somehow trigger their anxiety and affect their perceptions towards learning the language, in fact it is a nature part of life (Woodrow, 2006). English is not a new language need to be learned by Malaysian students. It has become the second official language after Malay Language. Therefore the demand to the need of knowing to use the language especially in communication is very high. Students managed to get excellent results in examination but fail to demonstrate the knowledge they have through speaking skills. It is believed the factors that may cause the anxiety rooted from their experience learning the language in the classroom. Previous research (Choy & Troudi, 2006) agreed with the fact that classroom is a place that could trigger most anxious feelings out of the students. The purposes of this study are. to investigate the factors that cause speaking anxiety in the English classroom and to observe variation of anxieties that each schools in the institution {flight have. Coping strategies are recommended to overcome the issue. This stddy is participated by two hundreds of students from PTPL College, Shah Alam. The findings from this study show that students are concerned on the tasks and activities related to speaking, the application of grammar and their self-beliefs in learning English. Students from School of Business Management & Professional (SBMP) have been identified to experience speaking anxiety the most compared to other three schools. A very useful and practical recommendation for teachers to help students to overcome speaking anxiety was obtained. It was suggested that for futher studies on this issue, teachers’ perspectives should be put into consideration.